Multivalent Interaction of Beta-Catenin With its Intrinsically Disordered Binding Partner Adenomatous Polyposis Coli - Rowling, Pamela J. E.; Murton, Ben L.; Du, Zhen; Itzhaki, Laura S. (Frontiers in Molecular Biosciences, 2022)
The Wnt signalling pathway plays key roles in cell proliferation, differentiation and fate decisions in embryonic development and maintenance of adult tissues, and the twelve Armadillo (ARM) repeat-containing protein beta-catenin acts as the signal transducer in this pathway. Here we investigate the interaction between beta-catenin’s ARM repeat domain and the intrinsically disordered protein adenomatous polyposis coli (APC). APC is a giant multivalent scaffold that brings together the different components of the so-called ‘beta-catenin destruction complex’, which drives beta-catenin degradation via the ubiquitin-proteasome pathway. Mutations and truncations in APC, resulting in loss of APC function and hence elevated beta-catenin levels and upregulation of Wnt signalling, are associated with numerous cancers including colorectal carcinomas. APC has a long intrinsically disordered region (IDR) that contains a series of 15-residue and 20-residue binding regions for beta-catenin. Here we explore the multivalent nature of the interaction of beta-catenin with the highest affinity APC repeat, both at equilibrium and under kinetic conditions. We use a combination of single-site substitutions, deletions and insertions to dissect the mechanism of molecular recognition and the roles of the three beta-catenin-binding subdomains of APC.